Legal Protection of Vehicle Users by Under Age (Minors) Viewed from The Perspective at Present Act No.22 of 2009 on Traffic and Transportation - Suwitno Suwitno (Jurnal Daulat Hukum, 2018)
The research problems are how the legal protection of motorists under the age of the offenses traffic violations and how efforts and the role of the police in dealing with traffic violations committed minors. Research result This is the legal protection of motorists under the age of criminal acts against traffic violations that should Criminal sanctions imposed on the child must be based on truth, justice, and child welfare. Criminal punishment or actions to be accountable and beneficial for children. The judge shall consider the situation of children, the state house, state of the environment, and social counselors report. Children who are no older than twelve (12) years, although with a criminal offense can not be put on trial the child. The effort and the role carried out by the police in tackling traffic offenses committed by children under age (minors) namely with the preventive and repressive efforts.Keywords: Legal Protection, Minors, Traffic Law.